Varying family planning strategies across age categories: differences in factors associated with current modern contraceptive use among youth and adult women in Luanda, Angola - Prata N; Bell S; Weidert K; Nieto-Andrade B; Carvalho A; Neves I (Dove Medical Press, 2016)
Ndola Prata,1 Suzanne Bell,1 Karen Weidert,1 Benjamin Nieto-Andrade,2 Adelaide Carvalho,3 Isilda Neves3 1Bixby Center for Population, Health and Sustainability, School of Public Health, University of California at Berkeley, Berkeley, CA, USA; 2Population Services International Angola, 3National Directorate of Public Health, Ministry of Health, Luanda, Angola Background: The objective of this study is to identify factors associated with current modern contraceptive use among Angolan women. By differentiating according to age groups (15–24 and 25–49 years), this study aimed to help family planning program planners better tailor interventions to improve utilization of modern contraception.Methods: A household survey was used to collect data from 1,545 women of reproductive age living in Luanda Province, Angola. Data on sociodemographic characteristics, reproductive behavior and intentions, contraceptive knowledge and use, and attitudes and beliefs regarding contraception and abortion were collected. The analyses were stratified based on age: 15–24 years (youth) and 25–49 years (adult). Multivariate logistic regression models were built for each age group, adding different subsets of variables in groups to see how relationships changed across the models.Results: Common factors associated with modern contraceptive use among all ages include education level, perceived contraceptive accessibility, contraceptive knowledge, communication with partner about family planning in last year, and self-efficacy. Exposure to family planning information in the media in the last few months, perceived partner approval of family planning, and marital status were all positively associated with current modern contraceptive use among women aged 15–24 years. Meanwhile, receiving information about family planning from a pharmacy in the last year was uniquely associated with current modern contraceptive use among women aged 25–49 years.Conclusion: Young women in Luanda, Angola seem to have a unique set of factors affecting their contraceptive use. These findings highlight the need for family planning programs to cater services and messages toward specific age groups. Keywords: contraceptive uptake, contraceptive access, contraceptive self-efficacy, partner communication